Analisis Sistem Pengelolaan Arsip Inaktif di PT Prima Mitra Elektrindo - Gadis Tabina (Pusat Riset dan Inovasi Nasional, 2024)
Records management processes that are not carried out according to procedures will result in the administration process within the company not being optimal. Therefore, the management of active and inactive records must be considered carefully. Management of inactive records must be carried out according to procedures which include storage, maintenance and destruction. This research uses a qualitative descriptive approach, namely by formulating problems that guide research to explore or photograph the social situation that will be researched thoroughly, broadly and in depth. The data sources in this research use primary and secondary sources obtained from observations, interviews and documentation. Meanwhile, secondary data was obtained through books, previous research, and journal articles related to the research. This research aims to find out how the inactive records management system at PT. Prima Mitra Elektrindo. The results of this research indicate that the records management system is inactive at PT. Prima Mitra Elektrindo is quite good even though there are several things that need attention in the inactive records management system, the process of destroying inactive records, and the process of maintaining inactive records. Such as infrastructure that supports management and following guidelines in the management process.